A life in the trees - Attenborough, Richard, 1926-; British Broadcasting Corporation (Wilmette : Films Inc., 1981)
Naturalist David Attenborough explores the evolution of primates in a range of geographic areas and explains the significance of binocular vision and grasping hand in successful adaptation to life in the trees
Keywords: Primates -- Evolution